Recovery from Strenuous Downhill Running in Young and Older Physically Active Adults - Hayashi, Koichiro; Leary, Miriam E.; Roy, Stephen J.; Laosiripisan, Jitanan; Pasha, Evan P.; Tanaka, Hirofumi (International Journal of Sports Medicine, 2019)
There is a well-conceived notion that rate of recovery from strenuous exercise gets slower with age. However, it is unclear whether older adults who exercise habitually demonstrate slower rates of recovery. We determined whether older adults who are physically active demonstrate slower rates of recovery from unaccustomed strenuous exercise compared with younger peers. Healthy young sedentary (n=10, 28±2 years), young endurance-trained (n=15, 27±2 years), and older endurance-trained (n=14, 58±2 years) men and women were studied. Participants performed 45 min of downhill running at 65% of their maximal oxygen consumption. Visual analog pain scores of muscle groups increased at 24, 48, and 72 h in all three groups (p<0.05), and changes in the muscular pain scale of the legs was smaller in the older trained group than in the young trained group. Maximum isometric strengths at 90° decreased in all groups at 24 h, but the recovery rates were not different at 72 h among the groups. Plasma creatine kinase activity and myoglobin concentration increased at 24 h following downhill running and returned to baseline at 48 h in both the young and older trained groups. The present findings are not consistent with the prevailing notion that older trained adults have a slower rate of recovery from strenuous exercise.
Keywords: muscle damage; aging; exercise